2013
DOI: 10.1002/ppap.201300014
|View full text |Cite
|
Sign up to set email alerts
|

Application of Poly(Acrylic Acid)‐Multiwalled Carbon Nanotube Composite for Enrichment of Rrace Hg(II)

Abstract: Poly(acrylic acid)‐multiwall carbon nanotubes (PAA‐MWCNTs) was synthesized and was used as a adsorbent for the preconcentration and removal of trace Hg(II) from aqueous solution. Microwave plasma technique was used to activate MWCNT surfaces, which induces the polymerization of acrylic acid on MWCNTs. Fourier transform infrared spectroscopy, Raman spectroscopy, X‐ray photoelectron spectroscopy, and thermogravimetric analysis demonstrated that acrylic acid monomer was polymerized on MWCNT surfaces. Due to the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Among several plasma‐deposited polymers investigated over the last two decades, thin films containing carboxylic acid groups (COOH) have received considerable attention with the aim, for instance, to improve the adhesion of surfaces to polymers or inorganic materials, to enhance cell adhesion and growth, to increase the adsorption of basic species and metals . Deposition processes are mostly performed using acrylic acid (AA) as thin film precursor.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among several plasma‐deposited polymers investigated over the last two decades, thin films containing carboxylic acid groups (COOH) have received considerable attention with the aim, for instance, to improve the adhesion of surfaces to polymers or inorganic materials, to enhance cell adhesion and growth, to increase the adsorption of basic species and metals . Deposition processes are mostly performed using acrylic acid (AA) as thin film precursor.…”
Section: Introductionmentioning
confidence: 99%
“…[9] Among several plasma-deposited polymers investigated over the last two decades, thin films containing carboxylic acid groups (COOH) have received considerable attention with the aim, for instance, to improve the adhesion of surfaces to polymers or inorganic materials, [10,11] to enhance cell adhesion and growth, [12] to increase the adsorption of basic species [13] and metals. [14] Deposition processes are mostly performed using acrylic acid (AA) as thin film precursor. Different studies demonstrated that, using both low [12,[15][16][17][18][19][20][21] and atmospheric [22][23][24][25][26][27][28] pressure plasmas, it is possible to tune the amount of COOH groups in the coatings by varying the plasma operational parameters.…”
Section: Introductionmentioning
confidence: 99%
“…The results are shown in Figure 10 . At 2943 cm −1 and 2875 cm −1 , they are the characteristic absorption peaks of methyl and methylene, which are mainly the characteristic chemical bonds of waterborne acrylic acid (the main component of the primer) [ 35 ]. The absorption peak at 1547 cm −1 belongs to -NH- stretching vibration peak, which belongs to the characteristic peak of melamine resin [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…In practice, there are not many cases of high concentration mercury ion contamination. According to the comprehensive sewage discharge standard GB8978-2005 in China, the concentration of mercury ions in the discharged sewage shall not exceed 0.05 mg•L −1 [22]. In this study, a composite material for treating lower concentrations of mercury ions was synthesized in order to further investigate the ability of the material to deal with actual mercury ion wastewater.…”
Section: Introductionmentioning
confidence: 99%